Stimulation of innate and adaptive immune cells with graphene oxide and reduced graphene oxide affect cancer progression - Yunus, Muhammad Amir; Ramli, Muhammad Mahyiddin; Osman, Nurul Huda; Mohamed, Rafeezul (Springer, 2021)
Sole nanomaterials or nanomaterials bound to specific biomolecules have been proposed to regulate the immune system. These materials have now emerged as new tools for eliciting immune-based therapies to treat various cancers. Graphene, graphene oxide (GO) and reduced GO (rGO) are the latest nanomaterials among other carbon nanotubes that have attracted wide interest among medical industry players due to their extraordinary properties, inert-state, non-toxic and stable dispersion in a various solvent. Currently, GO and rGO are utilized in various biomedical application including cancer immunotherapy. This review will highlight studies that have been carried out in elucidating the stimulation of GO and rGO on selected innate and adaptive immune cells and their effect on cancer progression to shed some insights for researchers in the development of various GO- and rGO-based immune therapies against various cancers.